Improving Student Mathematics Learning Outcomes Through the Problem Based Learning (PBL) Learning Model on Linear Program Material in Class XI SMA Negeri 1 Tigabinanga - Lola Ressa Br Tarigan; Mangaratua Marianus Simanjorang (Formosa Journal of Multidisciplinary Research, 2023)
This study aims to find out that the Problem Based Learning (PBL) learning model can improve the mathematics learning outcomes of class XI students of SMA Negeri 1 Tigabinanga on linear programming material. The subjects in this study were 34 students of class XI IPA 5 at SMA Negeri 1 Tigabinanga and the object of this study was to increase students' mathematics learning outcomes through the Problem Based Learning model. The research instruments used were tests and reflective journals. This research is a classroom action research (PTK) which lasts for two cycles. The results of data analysis were obtained from the results of students' mathematics learning which increased from cycle I to cycle II after applying the Problem Based Learning learning model. In the pre-test cycle I, the average class value was 60.35 and the classical completeness was 20.59%. The results of the post-test cycle I obtained an average value of 74.12 with a classical completeness of 47.06%. Where there is an increase of 13.77 with an N-Gain value of 0.23 which is included in the low category. And the second cycle for the pre-test obtained an average value of 66.44 with a classical completeness of 32.35%. Meanwhile, the post-test results obtained an average value of 85.26 with classical completeness of 88.24%. In cycle II, the average increase was 18.71 and the N-Gain value obtained was 0.50, which is included in the medium category and has reached an indicator of cycle success. So, based on the results of this study, the learning outcomes of class XI IPA 5 SMA Negeri 1 Tigabinanga can be increased by using the Problem Based Learning learning model.